2011
DOI: 10.1164/rccm.201009-1431oc
|View full text |Cite
|
Sign up to set email alerts
|

Exudate Macrophages Attenuate Lung Injury by the Release of IL-1 Receptor Antagonist in Gram-negative Pneumonia

Abstract: We conclude that recruited lung macrophages attenuate IL-1β-mediated acute lung injury in gram-negative pneumonia by release of IL-1ra.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
89
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(92 citation statements)
references
References 50 publications
1
89
1
1
Order By: Relevance
“…5,[35][36][37] Recent studies have identified a regulatory protective role for inflammatory monocytes in infectious diseases as they synthetize and secrete anti-inflammatory mediators, such as IL-1ra and prostaglandin E2. 8,9 However, the specific contribution of inflammatory monocytes to the regulation of inflammation in early phases of sepsis remains unclear. Our results have unveiled a key role these monocytes play in renal tissue protection via a CX3CR1-dependent adhesion of inflammatory monocytes to the renal vascular endothelium.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5,[35][36][37] Recent studies have identified a regulatory protective role for inflammatory monocytes in infectious diseases as they synthetize and secrete anti-inflammatory mediators, such as IL-1ra and prostaglandin E2. 8,9 However, the specific contribution of inflammatory monocytes to the regulation of inflammation in early phases of sepsis remains unclear. Our results have unveiled a key role these monocytes play in renal tissue protection via a CX3CR1-dependent adhesion of inflammatory monocytes to the renal vascular endothelium.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that inflammatory monocytes are involved in controlling inflammation in gram-negative pneumonia and abdominal infections. 8,9,[38][39][40][41][42] A lower number of inflammatory monocytes has been associated with increased lesions in the lung and in the intestinal lamina propria. 8,9,38,41 Other studies have shown that the CX3CR1/ CX3CL1 axis is involved in the pathogenesis of sepsis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…M2-polarised macrophages have been associated with tissue repair of the acutely inflamed lung [153]; however, experimental evidence of a similar role in respiratory viral disease is limited. Monocyte-derived alveolar macrophages were found to secrete hepatocyte growth factor (HGF), a potent lung epithelial cell mitogen, which induced proliferation of type II alveolar epithelial cells in a mouse IAV infection model [154,155].…”
Section: Resolution Of Lung Injury and Alveolar Regenerationmentioning
confidence: 99%
“…Consistent with the proinflammatory profile of airway casts was increased IL-1b, a recruiter of macrophages, and the associated increase in IL-1 receptor antagonist (23)(24)(25). In the context of cell death, elevated levels of IL-1a (see Figures E5 and E6), a cytokine that has a functional role in the nucleus in addition to its receptormediated actions, have been shown to be associated with cell necrosis rather than apoptosis (26).…”
Section: Cytokine Profile Of Plastic Bronchitis Casts Is Proinflammatorymentioning
confidence: 53%